Internet Use and Problematic Use in Seniors: A Comparative Study in Switzerland and Poland - Rochat, Lucien; Wilkosc-Debczynska, Monika; Zajac-Lamparska, Ludmila; Rothen, Stéphane; Andryszak, Paulina; Gaspoz, Julie; Colombo, Laura; Khazaal, Yasser; Achab, Sophia (Frontiers in Psychiatry, 2021)
Background: Seniors have been only little considered in studies examining problematic internet use and associated health issues, although they may present risk factors that make them particularly vulnerable for the development of problematic internet use. Objectives: (1) To compare internet use and problematic use among seniors in Switzerland and Poland; (2) To examine the relationships between problematic internet use, impulsivity traits and well-being as previous studies showed that internet can be used to cope with negative emotions or life dissatisfaction. Methods: A cross-sectional survey conducted between June 2016 and April 2017 with 264 older internet users aged above 60 years old recruited in Switzerland (88) and Poland (176) assessing sociodemographic variables, online activities, problematic internet use, impulsivity traits and well-being. Results: The two groups differed in their reported online activities in that Polish participants reported more searching for information and buying , whereas Swiss participants reported significantly greater problematic internet use than Polish participants. Finally, a multiple linear regression analysis performed on the whole sample indicated that lower-well being and being a Swiss participant were both significantly associated with greater problematic internet use, after age, gender, level of education, impulsivity traits have been controlled for. Discussion: Swiss seniors showed a more problematic internet use than Polish participants who focused more in their online activities on utility use of internet. The relationships between problematic internet use and well-being suggest that older adults use internet mainly to cope with negative emotion or life dissatisfaction. Socio-cultural differences that could account for these group differences as well as difference with young adults are also discussed.